Morphoanatomy and essential oil analysis of Baccharis trimera (Less.) DC. (Asteraceae) from Uruguay - Minteguiaga, Manuel (2018)
Baccharis trimera (Less.) DC. (Asteraceae), ?carqueja´, is a medicinal plant native from South America employed as decoction or infusion for the treatment of low to moderate ailments, and included in the Brazilian Pharmacopeia. This plant is also a rich source of essential oil (EO) valuable in the fragrance industry, mainly owing to carquejyl acetate, carquejol and several sesquiterpenic alcohols contributing to its characteristic aroma reminisce of rosewood. In this work, we report the EO composition, morpho-anatomical and histochemical characterization of B. trimera growing wild in Uruguay. 150 compounds were identified by gas chromatography-mass spectrometry (GC?MS), 79 of them not previously reported for this species, whose relative proportions varied according the season. Anatomically, the specimens analyzed did not present any leaves nor ribs between the wings. The epidermis presented polygonal cells with straight anticlinal walls, with anisocytic and less frequently anomocytic stomata. Non-glandular (multicellular, unistratified, with a characteristic elongated apex cell) and glandular (multicellular, bistratified, EO positive) trichomes were evidenced. The mesophyll at the wing level was isolateral with a central spongy parenchyma. Schyzogenous ducts with bistratified secretory epithelium (EO and polyphenols positive), were occasionally associated with the endodermis. The perimedullar parenchyma of the cladodes presented polyhedral pyramidal and prismatic crystals of calcium oxalate, according to previous reports.